Trends in the treatment of human papillomavirus-associated oropharyngeal carcinoma in Slovakia - Švajdová, Michaela; Dubinský, Pavol; Jeremić, Branislav; Vojtek, Vladimír; Barilíková, Gabriela; Selingerová, Iveta; Kazda, Tomáš (Neoplasma, 2024)
The optimal treatment of oropharyngeal cancer (OPC) associated with human papillomavirus (HPV) is currently a subject of clinical research. This questionnaire study investigated current trends in the treatment of HPV-associated (HPV+) OPC in Slovakia with the incorporation of deintensification of oncological treatment into routine clinical practice outside of clinical trials. The Slovak Cooperative Head and Neck Cancer Group (SCHNCG) developed a questionnaire aimed at identifying trends in the oncological treatment of HPV+ OPC intended for all radiation oncology (RO) facilities in Slovakia. Specialists in the field of RO responded to general questions about the character of their individual institutions as well as to 4 theoretical clinical scenarios (case reports) regarding the treatment of HPV+ OPC, focusing primarily on the applied dose of radiotherapy (RT), the extent of target volumes, and the type of concurrent chemotherapy (CHT). The questionnaire study involved 35 RO specialists from 14 institutions in Slovakia. Regarding primary chemoradiotherapy (CRT) in T1N1M0 HPV+ OPC, 16 respondents (45.7%) would consider de-escalation of the RT dose to <70 Gy. In the case of postoperative RT in pT1pN1M0 HPV+ OPC with negative resection margins (R0) and absent extracapsular extension (ECE), 4 physicians (11.4%) would consider de-escalation of the RT dose to <60 Gy in the tumor bed area, while the majority of the treating specialists (n=19, 54.3%) would omit concurrent CHT. In the case of primary RT in elderly patient with T2N1M0 HPV+ OPC, the same number of physicians (n=16, 45.7%) would consider de-escalation of the RT dose to <70 Gy, and 14 respondents (40.0%) would completely omit CHT. In a high-risk patient with T2N3M0 HPV+ OPC with a complete response after 3 cycles of induction chemotherapy (iCHT), none of the respondents would indicate a reduction in the RT dose to the area of the original tumor and lymphadenopathy to <60 Gy. The doses and extent of irradiated volumes in the treatment of HPV+ OPC in Slovakia vary among different institutions. The tendency to de-escalate RT doses and reduce doses of concurrent systemic therapy in Slovakia is high and there was also an observed trend to reduce the extent of radiation treatment fields.
Keywords: Human Papillomavirus Viruses; průzkumy a dotazníky; Papillomavirus Infections; Female; lidské papilomaviry; ženské pohlaví; Surveys and Questionnaires; Papillomaviridae; Slovakia; lidé; nádory orofaryngu; Male; Oropharyngeal Neoplasms; infekce papilomavirem; chemoradioterapie; Slovenská republika; mužské pohlaví; Chemoradiotherapy; Humans